Operational Concepts and Sharia Principles in the Management of Sharia Financial Institutions - Asyrofi, Muhammad Zuhdi; Albahi, Muhammad; Andrini, Rozi (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Islamic Financial Institutions (IFIs) are financial entities that operate in accordance with Islamic Sharia principles, which prohibit practices such as riba (usury), gharar (uncertainty), and maisir (gambling), while upholding social and economic justice. This article aims to provide a comprehensive explanation of the operational concepts and Sharia principles that underpin the management of Islamic financial institutions, and to analyze their implementation within the modern financial system. This study employs a qualitative approach, drawing on sources from the Qur'an, Hadith, fatwas issued by the National Sharia Board of the Indonesian Ulema Council (DSN-MUI), and regulations issued by the Financial Services Authority (OJK). The findings indicate that the operations of Islamic financial institutions are founded upon three main pillars: justice ('adl), public interest (maslahah), and transparency (amanah). These principles are implemented through various Sharia contracts such as mudharabah (profit-sharing), musyarakah (partnership), murabahah (cost-plus sale), ijarah (leasing), and wakalah (agency). Sharia principles serve not only as a legal and moral foundation but also shape the institution's risk management system, Sharia governance, and Islamic Corporate Social Responsibility (ICSR). Therefore, the management of Islamic financial institutions is not merely profit-oriented but also grounded in spiritual, social, and sustainable economic values for the ummah. This study is expected to enrich academic literature on strengthening Sharia governance and to provide recommendations for regulators and practitioners to enhance the quality of Sharia compliance within the financial sector.